The ‘local content’ concept in public procurement: global trends in the development of public procurement law on the example of the USA, South Africa and Poland - Kola, Jarosław (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
In recent years, the approach to the functions of law in economy has significantly changed and is perceived more and more often as a tool (instrument) to accomplish various strategic goals of development policy. The aim of the paper is to discuss such legislative efforts as the latest and, given the EU perspective, the most interesting examples of instrumentalizing public procurement through the implementation of the ‘local content’ concept. Key observations from characterization of the US and South Africa relevant regulations were considered with respect to the legal environment in the EU and Poland. The main goal of this paper is to advance conclusions concerning the legal framework in which enacting local content requirements (LCRs) would be acceptable in the light of EU law. The paper shows that the applying of LCRs in public procurement procedures may be permitted in the EU, albeit to a limited extent. In the tender procedures taking place in the EU Member States, such solutions must respect the principle of proportionality in line with the EU public procurement law, stem from objectively justified needs of the contracting authority and – in all certainty – cannot pursue protectionist interests by limiting access to the procedure for contractors who do not meet certain LCRs.